Fuzzy Graphs With Equal Fuzzy Domination And Independent Domination Numbers - A. Nagoorgani; P. Vijayalakshmi (University of Bandar Lampung (UBL), 2013)
The basic definitions of fuzzy independent set, fuzzy dominating set,and fuzzy independent dominating sets are discussed. The aim of this paper is to find on what conditions the fuzzy graph has equal domination number and independent domination number. It is discussed briefly and also when the fuzzy graph is domination perfect is proved. Finally, the independent domination number for a connected fuzzy graph is obtained.